2014
DOI: 10.1523/jneurosci.2341-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

p140Cap Regulates Memory and Synaptic Plasticity through Src-Mediated and Citron-N-Mediated Actin Reorganization

Abstract: A major challenge in the neuroscience field is the identification of molecules and pathways that control synaptic plasticity and memory. Dendritic spines play a pivotal role in these processes, as the major sites of excitatory synapses in neuronal communication. Previous studies have shown that the scaffold protein p140Cap localizes into dendritic spines and that its knockdown negatively modulates spine shape in culture. However, so far, there is no information on its in vivo relevance. By using a knock-out mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(84 citation statements)
references
References 49 publications
5
79
0
Order By: Relevance
“…Given the crucial role of actin dynamics in neuronal morphology not only during spine morphogenesis but also in activity-dependent structural plasticity, and a recently identified function of p140Cap in learning and long-term potentiation/long-term depression using p140Cap-knockout mice [37], our results raise the possibility that endophilin A1 is also involved in regulation of synaptic plasticity and memory.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Given the crucial role of actin dynamics in neuronal morphology not only during spine morphogenesis but also in activity-dependent structural plasticity, and a recently identified function of p140Cap in learning and long-term potentiation/long-term depression using p140Cap-knockout mice [37], our results raise the possibility that endophilin A1 is also involved in regulation of synaptic plasticity and memory.…”
Section: Discussionmentioning
confidence: 66%
“…It is also reported that overstimulation of NMDA receptors removes cortactin and thereby collapses dendritic spines, whereas stimulation with neurotrophic factors redistributes cortactin from dendritic shafts to spines to solidify synaptic transmission [35]. As p140Cap is able to regulate cortactin phosphorylation by Src and associate with cortactin in neurons [26,36,37], next we investigated whether endophilin A1 regulates reorganization of the actin cytoskeleton to drive spine morphogenesis and whether cortactin acts downstream of the endophilin A1-p140Cap pathway.…”
Section: Endophilin A1 Regulates Actin Cytoskeleton Reorganization Inmentioning
confidence: 99%
“…The integrity of this macromolecular complex appears to be fundamental for both structural and functional synaptic plasticity. Indeed, p140Cap − / − mice display similar defects in episodic memory and are impaired in LTP and in LTD. 59 These data provide new mechanistic insights as to SNAP-25 involvement in synaptopathies that go beyond the protein's known roles in presynaptic function, indicating a protein role as a postsynaptic structural hub. Indeed, the activity-driven spine remodeling is defective in neuronal networks constitutively developing in the presence of reduced levels of SNAP-25, as it might presumably occur in human pathologies, such as schizophrenia, where both a reduction of SNAP-25 expression 15 and a reduction in dendritic spine density 60 have been described.…”
Section: Discussionmentioning
confidence: 84%
“…SNAP-25 wild-type and SNAP-25 heterozygous male mice 61 were housed in cages with free access to food and water at 22°C and with a 12-h alternating light/dark cycle. Genotyping was performed by PCR as described in Washbourne et al 61 p140Cap wild-type and knockout mice strain is described in Repetto et al 59 Cell cultures. Mouse hippocampal or rat hippocampal and cortical neurons were prepared from E18 fetal SNAP-25 heterozygous (Het) or wild-type (wt) littermates C57BL/6 mice as described in Bartlett and Banker 62 with slight modifications.…”
Section: Methodsmentioning
confidence: 99%
“…3E). Based on recent studies indicating that Srcin1 plays a critical role in regulating synaptic plasticity in the hippocampus and spatial memory (28,29), and on the fact that Srcin1 is the most highly regulated among the genes that show reciprocal changes in H3R2me2a and H3K4me3, we focused subsequent attention on cocaine regulation of Srcin1.…”
Section: Significancementioning
confidence: 99%